Abundance of kinless hubs within soil microbial networks are associated with high functional potential in agricultural ecosystems. (September 2020) - Shi, Yu; Delgado-Baquerizo, Manuel; Li, Yuntao; Yang, Yunfeng; Zhu, Yong-Guan; Peñuelas, Josep; Chu, Haiyan
Highlights: We built a correlation network using fungal and bacterial taxa. Kinless hubs were highly positively correlated with the abundance of functional genes. SEM results highlighted the positive effect of kinless hubs on the functional genes. Abstract: Microbial taxa within complex ecological networks can be classified by their universal roles based on their level of connectivity with other taxa. Highly connected taxa within an ecological network (kinless hubs) are theoretically expected to support higher levels of ecosystem functions than less connected taxa (peripherals). Empirical evidence of the role of kinless hubs in regulating the functional potential of soil microbial communities, however, is largely unexplored and poorly understood in agricultural ecosystems. Here, we built a correlation network of fungal and bacterial taxa using a large-scale survey consisting of 243 soil samples across functionally and economically important agricultural ecosystems (wheat and maize); and found that the relative abundance of taxa classified as kinless hubs within the ecological network are positively and significantly correlated with the abundance of functional genes including genes for C fixation, C degradation, C methanol, N cycling, P cycling and S cycling. Structural equation modeling of multiple soil properties further indicated that kinless hubs, but not provincial, connector or peripheral taxa, had direct significant and positive relationships with the abundance of multiple functional genes. Our findings provide novel evidence that the relative abundance of soil taxa classified as kinless hubs within microbial networks are associated with high functional potential, with implications for understanding and managing (through manipulating microbial key species) agricultural ecosystems at a large spatial scale.